Method for manufacturing a polarizing plate with a retardation layer

JP7633792B2Active Publication Date: 2025-02-20NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020171083
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-09
Publication Date
2025-02-20
Estimated Expiration
2040-10-09

AI Technical Summary

Benefits of technology

【0006】 本発明の実施形態によれば、第一保護フィルムと、偏光板と、位相差層と、第二保護フィルムとをこの順に有する積層体に対し、所定の条件において加湿処理を施すことにより、偏光板および位相差層が所定の厚みを有していても、反りが抑制された位相差層付偏光板を歩留まりよく製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633792000004
    Figure 0007633792000004
  • Figure 0007633792000005
    Figure 0007633792000005
  • Figure 0007633792000006
    Figure 0007633792000006
Patent Text Reader

Abstract

To provide a polarizing plate fitted with a retardation layer the warp of which is suppressed, with good yield.SOLUTION: A method for manufacturing a polarizing plate fitted with a retardation layer pertaining to an embodiment of the present invention includes: preparing a laminate having a first protective film, a polarizing plate that includes a polarizer and a protective layer arranged on least one side of the polarizer, a retardation layer, and a second protective film in the order stated, the sum total of the thickness of the polarizing plate and the thickness of the retardation layer being 50 μm or less, the ratio of the thickness of the polarizing plate to the thickness of the retardation layer being 5 or greater; and wet-processing the laminate while being placed on a placement plane under an environment where the laminate contains 10.5 g / m3 or more of water vapor. The laminate is placed on the placement plane such that the principal surface of the laminate is at an angle.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polarizing plate with a retardation layer. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), are rapidly becoming widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used (e.g., Patent Document 1). In recent years, the possibility of bending, bending, folding, and rolling up image display devices using a flexible substrate (e.g., a resin substrate) has been studied. As a retardation layer-attached polarizing plate to be used in such image display devices, a thin retardation layer-attached polarizing plate is desired. However, a thin retardation layer-attached polarizing plate has a problem in that it is prone to warping. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the prior art, and a main object of the present invention is to provide a retardation layer-attached polarizing plate with reduced warping with a high yield. [Means for solving the problem]

[0005] According to an embodiment of the present invention, there is provided a method for producing a polarizing plate with a retardation layer, which comprises preparing a laminate having a first protective film, a polarizing plate including a polarizer and a protective layer disposed on at least one side of the polarizer, a retardation layer, and a second protective film in this order, the total thickness of the polarizing plate and the retardation layer being 50 μm or less, and the ratio of the thickness of the polarizing plate to the thickness of the retardation layer being 5 or more, and disposing the laminate in a state where the laminate is placed on a placement surface and the laminate is heated to a temperature of 10.5 g / m2 or less to obtain a laminate having a water vapor content of 10.5 g / m2 or less. 3 The laminate is placed in the above-mentioned environment to be humidified, and the laminate is placed with the main surface of the laminate at an angle to the placement surface. In one embodiment, the production method includes laminating the polarizing plate and the retardation layer to obtain a laminate precursor. In one embodiment, the production method includes cutting the laminate precursor into sheets. In one embodiment, the humidification treatment is carried out with a plurality of the laminates arranged side by side. In one embodiment, the first protective film has a moisture permeability of 30 g / m at 40° C. and 92% RH. 2 Less than 24 hours. In one embodiment, the second protective film has a moisture permeability of 30 g / m at 40° C. and 92% RH. 2 Less than 24 hours. In one embodiment, the production method includes laminating the polarizing plate and the retardation layer while transporting them with rolls. In one embodiment, the production method includes laminating the polarizing plate and the retardation layer using an active energy ray-curable adhesive. In one embodiment, the active energy ray-curable adhesive has a thickness of 0.4 μm or more after curing. In one embodiment, the laminate has a pressure-sensitive adhesive layer arranged on the side of the retardation layer on which the polarizing plate is not arranged, and the weight increase per unit area of ​​the laminated portion of the polarizing plate, the retardation layer, and the pressure-sensitive adhesive layer due to the humidification treatment is 0.1% or more. In one embodiment, the humidification treatment time is 6 hours or more. In one embodiment, the amount of water vapor during the humidification treatment is 10.5 g / m 3 ~30g / m 3 It is. In one embodiment, the manufacturing method further comprises: 3 This includes laminating under the following conditions: In one embodiment, the amount of water vapor during the humidification treatment is 0.5 g / m less than the amount of water vapor during lamination of the polarizing plate and the retardation layer. 3 More than that. In one embodiment, the retardation layer or the protective layer has a moisture permeability of 300 g / m at 40° C. and 92% RH. 2 -24 hours or more. In one embodiment, in the polarizing plate, a protective layer is arranged only on the side of the polarizer on which the retardation layer is not arranged. In one embodiment, the center of gravity in the thickness direction of the polarizer is located on the retardation layer side of the center of gravity in the thickness direction of a laminated portion of the polarizing plate and the retardation layer. In one embodiment, the retardation layer is a layer in which a liquid crystal compound is aligned and fixed. Effect of the Invention

[0006] According to an embodiment of the present invention, by subjecting a laminate having a first protective film, a polarizing plate, a retardation layer, and a second protective film in this order to a humidification treatment under specified conditions, it is possible to produce a retardation layer-attached polarizing plate with reduced warping with good yield, even if the polarizing plate and the retardation layer have a specified thickness. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view showing an outline of a laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an outline of the configuration of a laminate according to a second embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a warped state of a laminate precursor. [Figure 4] FIG. 2 is a cross-sectional view showing an example of a laminated portion from a polarizing plate to a pressure-sensitive adhesive layer. [Diagram 5] FIG. 2 is a cross-sectional view showing an example of a state in which a laminate is placed on a placement surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0010] A method for manufacturing a polarizing plate with a retardation layer according to one embodiment of the present invention includes preparing a laminate having a polarizing plate including a polarizer and a retardation layer, and placing the laminate on a mounting surface under a predetermined environment.

[0011] A. Laminate FIG. 1 is a schematic cross-sectional view showing an outline of the laminate according to the first embodiment of the present invention. The laminate 100 has a first protective film 31, a polarizing plate 10, a retardation layer 20, and a second protective film 32 in this order from the viewing side. In the illustrated example, the polarizing plate 10 includes a polarizer 11 and a protective layer 12 arranged on the viewing side of the polarizer 11 (the side on which the retardation layer 20 is not arranged), and no protective layer is arranged between the polarizer 11 and the retardation layer 20. According to such a form, for example, the thickness, total thickness, thickness ratio, and moisture permeability of the polarizing plate described later can be satisfactorily achieved. Typically, the center of gravity in the thickness direction of the polarizer is located on the retardation layer side of the center of gravity in the thickness direction of the laminated portion of the polarizing plate and the retardation layer.

[0012] Although not shown, a protective layer may further be included on the other side of the polarizer 11 (between the polarizer 11 and the retardation layer 20).

[0013] 2 is a schematic cross-sectional view showing an outline of the structure of a laminate according to a second embodiment of the present invention. In the first embodiment, the retardation layer 20 is a single layer, whereas in the second embodiment, the retardation layer 20 has a laminated structure including a first retardation layer 21 and a second retardation layer 22. Unlike the illustrated example, the retardation layer 20 may have a laminated structure of three or more layers.

[0014] Although not shown, the laminate may further have other functional layers. The type, characteristics, number, combination, arrangement, etc. of the functional layers that the laminate may have can be appropriately set according to the purpose. For example, the laminate may further have a conductive layer or a conductive layer-attached isotropic substrate. The conductive layer or the conductive layer-attached isotropic substrate is typically arranged between the retardation layer 20 and the second protective film 32. Note that a laminate (polarizing plate with retardation layer) having a conductive layer or a conductive layer-attached isotropic substrate is applied to, for example, a so-called inner touch panel type input display device in which a touch sensor is incorporated inside an image display panel. As another example, the laminate may further have other retardation layers. The optical characteristics (for example, refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other retardation layers can be appropriately set according to the purpose. As a specific example, the viewing side of the polarizer 11 may be provided with other retardation layers (typically, a layer imparting an (elliptical) polarization function, a layer imparting an ultra-high retardation) that improve visibility when viewed through polarized sunglasses. By having such layers, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the obtained polarizing plate with a retardation layer can be suitably applied to image display devices that can be used outdoors.

[0015] Each member constituting the laminate may be laminated via any suitable adhesive layer (not shown). Specific examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. For example, the first protective film 31 is attached to the polarizing plate 10 via a pressure-sensitive adhesive layer. The first protective film 31 may be peeled off before the retardation layer-attached polarizing plate obtained by the embodiment of the present invention is used (before being laminated on an image display panel) or during the manufacturing process of the final product (image display device), or may be mounted on the final product as it is.

[0016] For example, the second protective film 32 is attached to the retardation layer 20 via an adhesive layer. In practice, the second protective film 32 can function as a release film (separator) that is temporarily attached until the retardation layer-attached polarizing plate obtained by the embodiment of the present invention is used. By temporarily attaching the release film, for example, the adhesive layer is protected and the laminate can be formed into a roll.

[0017] For example, the retardation layer 20 is attached to the polarizing plate 10 via an adhesive layer (preferably, an active energy ray curable adhesive). When the retardation layer 20 has a laminated structure of two or more layers, each retardation layer is attached to the polarizing plate 10 via an adhesive layer (preferably, an active energy ray curable adhesive).

[0018] A-1. Polarizing plate The polarizing plate includes a polarizer and a protective layer. The thickness of the polarizing plate depends on the number of protective layers included, but is preferably 20 μm or more, more preferably 25 μm or more. On the other hand, the thickness of the polarizing plate is preferably 40 μm or less, more preferably 36 μm or less, and even more preferably 33 μm or less. In addition, when an adhesive layer is used when laminating the polarizer and the protective layer, the thickness of the adhesive layer is not included in the thickness of the polarizing plate.

[0019] The polarizer is typically a resin film containing a dichroic material (e.g., iodine). As described above, examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA)-based films, partially formalized PVA-based films, and partially saponified ethylene-vinyl acetate copolymer-based films.

[0020] The thickness of the polarizer is preferably 15 μm or less, more preferably 12 μm or less, and further preferably 10 μm or less, while the thickness of the polarizer is preferably 1 μm or more.

[0021] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 42.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0022] The protective layer may be formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of the material that is the main component of the film include cellulose resins such as triacetyl cellulose (TAC) and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates.

[0023] The retardation layer-attached polarizing plate obtained by the embodiment of the present invention is typically disposed on the viewing side of an image display device, and the protective layer 12 is disposed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat (HC) treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary.

[0024] The thickness of the protective layer 12 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm. When the above-mentioned surface treatment is performed, the thickness of the protective layer 12 includes the thickness of the surface treatment layer.

[0025] In one embodiment, the protective layer (not shown) disposed between the polarizer 11 and the retardation layer 20 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the protective layer disposed between the polarizer 11 and the retardation layer 20 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm.

[0026] The polarizing plate may be produced by any suitable method. Specifically, the polarizing plate may include a polarizer produced from a single-layer resin film, or may include a polarizer obtained by using a laminate of two or more layers.

[0027] The method for producing a polarizer from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, or the like. A polarizing plate can be obtained by laminating a protective layer on at least one side of the obtained polarizer. Such a production method is well known and commonly used in the art, and therefore a detailed description thereof will be omitted.

[0028] Specific examples of polarizers obtained using the laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and achieve high optical properties. At the same time, by increasing the orientation of the PVA in advance, problems such as a decrease in the orientation or dissolution of the PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules can be disturbed and the orientation can be reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained through a process in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by the drying shrinkage treatment.The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0029] A-2. Retardation layer The thickness of the retardation layer depends on its structure (whether it is a single layer or has a laminated structure), but is preferably 8 μm or less, more preferably 5 μm or less. On the other hand, the thickness of the retardation layer is, for example, 1 μm or more. In addition, when the retardation layer has a laminated structure, the "thickness of the retardation layer" means the total thickness of each retardation layer. Specifically, the "thickness of the retardation layer" does not include the thickness of the adhesive layer.

[0030] As the retardation layer, a liquid crystal compound alignment solidified layer (liquid crystal alignment solidified layer) is preferably used. By using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. Therefore, a polarizing plate with a retardation layer can be significantly thinned. In this specification, the "alignment solidified layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment hardened layer obtained by hardening a liquid crystal monomer as described later. In the retardation layer, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the retardation layer (homogeneous alignment).

[0031] The liquid crystal alignment solidified layer can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.

[0032] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0033] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.

[0034] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.

[0035] As described above, the retardation layer 20 may be a single layer, or may have a laminated structure of two or more layers.

[0036] As shown in FIG. 1, in one embodiment in which the retardation layer 20 is a single layer, the retardation layer 20 can function as a λ / 4 plate. Specifically, the Re(550) of the retardation layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 160 nm. The thickness of the retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the retardation layer is the above-mentioned liquid crystal alignment solidified layer, the thickness is, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably 44° to 46°. In this embodiment, the retardation layer preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. In this embodiment, the laminate may further include a layer (another retardation layer, not shown) that is disposed between the retardation layer 20 and the second protective film 32 and exhibits refractive index characteristics of nz>nx=ny.

[0037] In another embodiment in which the retardation layer 20 is a single layer, the retardation layer 20 can function as a λ / 2 plate. Specifically, the Re(550) of the retardation layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 230 nm to 280 nm. The thickness of the retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. When the retardation layer is the above-mentioned liquid crystal alignment solidified layer, the thickness is, for example, 2.0 μm to 4.0 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 12° to 16°.

[0038] As shown in FIG. 2, when the retardation layer 20 has a laminated structure, the retardation layer 20 has, for example, a two-layer laminated structure in which a first retardation layer (H layer) 21 and a second retardation layer (Q layer) 22 are arranged in order from the polarizer side. The H layer can typically function as a λ / 2 plate, and the Q layer can typically function as a λ / 4 plate. Specifically, Re(550) of the H layer is preferably 200 nm to 300 nm, more preferably 220 nm to 290 nm, and even more preferably 230 nm to 280 nm; Re(550) of the Q layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and even more preferably 110 nm to 150 nm. The thickness of the H layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. When the H layer is the above-described liquid crystal alignment cured layer, its thickness is, for example, 2.0 μm to 4.0 μm. The thickness of the Q layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the Q layer is the above-described liquid crystal alignment cured layer, its thickness is, for example, 1.0 μm to 2.5 μm. In the present embodiment, the angle formed by the slow axis of the H layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 12° to 16°; the angle formed by the slow axis of the Q layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 72° to 76°. When the retardation layer 20 has a laminated structure, each layer (for example, the H layer and the Q layer) may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light.

[0039] The retardation layer 20 (each layer when having a laminated structure) typically exhibits a refractive index characteristic showing a relationship of nx>ny=nz. Note that “ny=nz” includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range not impairing the effects of the present invention, ny>nz or ny<nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3.

[0040] As described above, the retardation layer is preferably a liquid crystal alignment solidified layer. The liquid crystal compound may be, for example, a liquid crystal compound (nematic liquid crystal) whose liquid crystal phase is a nematic phase. For example, a liquid crystal polymer or a liquid crystal monomer may be used as such a liquid crystal compound. The liquid crystal compound may exhibit liquid crystallinity by either lyotropic or thermotropic mechanism. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.

[0041] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the liquid crystal monomer can be polymerized or crosslinked (i.e., cured) to fix the alignment state of the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other to fix the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.

[0042] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0043] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. As the liquid crystal monomer, a nematic liquid crystal monomer is preferable.

[0044] A-3. Relationship between the thickness of the polarizing plate and the retardation layer The sum of the thickness of the polarizing plate and the thickness of the retardation layer (hereinafter, sometimes simply referred to as "total thickness") is 50 μm or less, preferably 45 μm or less, and more preferably 40 μm or less. On the other hand, the total thickness is, for example, 25 μm or more.

[0045] The ratio of the thickness of the polarizing plate to the thickness of the retardation layer (thickness of polarizing plate / thickness of retardation layer, hereinafter sometimes simply referred to as "thickness ratio") is 5 or more, preferably 8 or more, and more preferably 10 or more. On the other hand, the thickness ratio is preferably 30 or less, and more preferably 25 or less.

[0046] It can be said that the laminate used in the manufacturing method according to the embodiment of the present invention has a small total thickness and a large ratio of the thickness of the polarizing plate to the total thickness (a small ratio of the thickness of the retardation layer). The present inventors have found that when the total thickness and the thickness ratio are within the above-mentioned predetermined range, the above-mentioned warping problem is likely to occur. More specifically, when the difference between the thickness of the polarizing plate and the thickness of the retardation layer is not large, and when the thickness of the polarizing plate is excessively large, the warping problem is unlikely to occur in the polarizing plate with the retardation layer. Based on such new findings, the present inventors have intensively studied the suppression of warping and found that the manufacturing method according to the embodiment of the present invention can efficiently suppress warping.

[0047] A-4. First protective film The first protective film 31 may be formed of any appropriate material. Specific examples of the forming material include polyester-based polymers such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose; polycarbonate-based polymers; (meth)acrylic polymers such as polymethyl methacrylate; and cycloolefin-based polymers such as polynorbornene. These may be used alone or in combination of two or more.

[0048] The first protective film has a moisture permeability of 30 g / m at 40°C and 92% RH. 2 - 24h or less is preferable, and 20g / m 2 24h or less. With such a first protective film, moisture is appropriately added to the laminate (preferably, the polarizer) in the humidification treatment described later, and a retardation layer-attached polarizing plate with suppressed warping can be obtained. On the other hand, the moisture permeability of the first protective film at 40°C and 92% RH is, for example, 5 g / m 2 -24 hours or more.

[0049] The thickness of the first protective film is preferably from 15 μm to 50 μm, and more preferably from 25 μm to 40 μm.

[0050] As described above, the first protective film 31 can be attached to the polarizing plate 10 via an adhesive layer. Any appropriate structure can be adopted for the adhesive layer. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more kinds. The base resin is preferably an acrylic resin (specifically, the adhesive layer is preferably composed of an acrylic adhesive). The thickness of the adhesive layer is, for example, 5 μm to 15 μm. The storage modulus of the adhesive layer at 25° C. is, for example, 1.0×10 5 Pa~1.0×10 7 It is Pa.

[0051] In one embodiment, a laminate in which the pressure-sensitive adhesive layer is formed on a first protective film (hereinafter referred to as a "surface protective film") is used. The thickness of the surface protective film is preferably 30 μm to 60 μm, and more preferably 30 μm to 50 μm. As described above, when the first protective film is peeled off, it can be peeled off together with the pressure-sensitive adhesive layer (together with the surface protective film).

[0052] A-5. Secondary protective film The second protective film 32 may be made of any suitable plastic film. Specific examples of the plastic film include a polyethylene terephthalate (PET) film, a polyethylene film, and a polypropylene film. As described above, the second protective film 32 may function as a separator. Specifically, a plastic film whose surface is coated with a release agent is preferably used as the second protective film 32. Specific examples of the release agent include a silicone-based release agent, a fluorine-based release agent, and a long-chain alkyl acrylate-based release agent.

[0053] The second protective film has a moisture permeability of 30 g / m at 40°C and 92% RH. 2 - 24h or less is preferable, and 20g / m 2 By using such a second protective film, moisture is appropriately added to the laminate (preferably, the polarizer) in the humidification treatment described later, and a retardation layer-attached polarizing plate with suppressed warping can be obtained. On the other hand, the moisture permeability of the second protective film at 40° C. and 92% RH is, for example, 5 g / m 2 -24 hours or more.

[0054] The thickness of the second protective film is preferably from 20 μm to 80 μm, and more preferably from 35 μm to 55 μm.

[0055] A-6. Preparation of laminate The laminate 100 can be obtained, for example, by laminating a polarizing plate 10 and a retardation layer 20 to prepare a laminate precursor, and then laminating a first protective film 31 and a second protective film 32 onto the obtained laminate precursor.

[0056] The polarizing plate 10 and the retardation layer 20 are laminated, for example, while they are being transported by rolls (so-called roll-to-roll). The lamination is typically performed by transferring a liquid crystal alignment solidified layer formed on a substrate. As shown in FIG. 2, when the retardation layer has a laminated structure, each retardation layer may be laminated (transferred) sequentially onto the polarizing plate, or a laminate of retardation layers may be laminated (transferred) onto the polarizing plate.

[0057] The transfer is performed, for example, using an active energy ray curable adhesive. The thickness of the active energy ray curable adhesive after curing (thickness of the adhesive layer) is preferably 0.4 μm or more, more preferably 0.4 μm to 3.0 μm, and even more preferably 0.6 μm to 1.5 μm. The warping of the retardation layer-attached polarizing plate having the above-mentioned predetermined total thickness and thickness ratio is mainly caused by the adhesive used for laminating the polarizing plate and the retardation layer (specifically, shrinkage during curing of the active energy ray curable adhesive), and warping may occur in the laminate precursor obtained by laminating the polarizing plate 10 and the retardation layer 20.

[0058] Fig. 3 is a cross-sectional view showing an example of a warped state of a laminate precursor. In Fig. 3, hatching is omitted from the cross section of the laminate precursor to make the drawing easier to see. In the example shown in Fig. 3, a convex warp occurs in the laminate precursor 90 on the polarizing plate 10 side. The warp tends to occur along the absorption axis direction of the polarizing plate 10 (polarizer 11).

[0059] The laminate of the polarizing plate 10 and the retardation layer 20 has a water vapor content (A1) of 10.2 g / m 3 It is preferable that the lamination is performed under the following conditions: The amount of water vapor (A1) during lamination is more preferably 6.0 g / m 3 ~10.0g / m 3 and more preferably 8.0 g / m 3 ~9.5g / m 3 By performing lamination under an environment in which the amount of water vapor (A1) is in such a range, for example, the effect of the humidification treatment described below becomes remarkable. Such an amount of water vapor (A1) in lamination can be realized, for example, by changing the relative humidity according to the temperature in the range of 18°C ​​to 25°C. For example, when the temperature is 18°C, the amount of water vapor (A1) can be realized by setting the relative humidity to 65% RH or less; for example, when the temperature is 20°C, the amount of water vapor (A1) can be realized by setting the relative humidity to 55% RH or less; and for example, when the temperature is 23°C, the amount of water vapor (A1) can be realized by setting the relative humidity to 45% RH or less. The lower limit of the relative humidity can be, for example, 30% RH.

[0060] In one embodiment, the moisture permeability of either the protective layer 12 or the retardation layer 20 at 40°C and 92% RH is preferably 300 g / m2·24h or more, more preferably 400 g / m2·24h to 1000 g / m2·24h, and even more preferably 400 g / m2·24h to 800 g / m2·24h. If either the protective layer 12 or the retardation layer 20 has such moisture permeability, the effect of the humidification treatment described below can be significantly obtained.

[0061] As described above, when the laminate further has other functional layers (for example, a conductive layer, other retardation layers), the functional layers can be laminated or formed at predetermined positions by any appropriate method.

[0062] The laminate precursor having at least the polarizing plate 10 and the retardation layer 20 is laminated with the first protective film 31, for example, by bonding the above-mentioned surface protective film. The laminate precursor is laminated with the second protective film 32, for example, by using an adhesive. The thickness of the adhesive (the thickness of the adhesive layer disposed between the retardation layer 20 and the second protective film 32) is, for example, 10 μm to 20 μm.

[0063] B. Humidification treatment The laminate is subjected to a humidification treatment. By subjecting the laminate to a humidification treatment, moisture is added to the laminate (preferably the polarizer), and a retardation layer-attached polarizing plate with suppressed warping can be obtained. For example, the laminate can be humidified to a temperature of 10.5 g / m 3 By placing the substrate in the above environment, a humidification treatment is performed. The amount of water vapor (A2) during the humidification treatment is preferably 10.5 g / m 3 ~30g / m 3 and more preferably 11 g / m 3 ~20g / m 3 It is.

[0064] The amount of water vapor (A2) during the humidification process can be realized, for example, by setting the relative humidity to 80% RH or more when the temperature is 18° C., or by setting the relative humidity to 60% RH or more when the temperature is 20° C., or by setting the relative humidity to 50% RH or more when the temperature is 23° C. The upper limit of the relative humidity can be, for example, 100% RH.

[0065] In one embodiment, the laminate is subjected to a humidification treatment in an environment satisfying an amount of water vapor larger than the above amount of water vapor (A1). More specifically, the difference between the amount of water vapor (A2) during the humidification treatment and the above amount of water vapor (A1) is 0.5 g / m 3 More preferably, it is 1.0 g / m or more.3 ~28g / m 3 and more preferably 1.0 g / m 3 ~12g / m 3 and particularly preferably 1.5 g / m 3 ~10g / m 3 and most preferably 1.5 g / m 3 ~8g / m 3 By humidifying under such conditions, an appropriate amount of moisture can be imparted to the laminate. More specifically, moisture can be imparted to the laminate without causing the laminate to shrink. If too much moisture is imparted to the laminate in the humidifying treatment, for example, warping in a direction opposite to the initial warping and / or warping in a direction perpendicular to the initial warping direction may occur.

[0066] In one embodiment, the laminate is preferably subjected to a humidification treatment so that the weight per unit area of ​​the laminated portion from the polarizing plate to the adhesive layer increases by 0.1% or more. The weight increase per unit area of ​​the laminated portion from the polarizing plate to the adhesive layer due to the humidification treatment is more preferably 0.1% to 2.0%, further preferably 0.1% to 1.0%, and particularly preferably 0.1% to 0.5%. By setting the weight increase within such a range, the polarizer can absorb a desired amount of moisture. As a result, the warping of the obtained retardation layer-attached polarizing plate can be effectively suppressed. Here, the laminated portion from the polarizing plate to the adhesive layer refers to, for example, a laminated portion 80 of the polarizing plate 10, the adhesive layer 40, the retardation layer 20 (including the adhesive layer when the laminated structure is present), and the adhesive layer 50, as shown in FIG. 4. In FIG. 4, hatching is omitted from the cross section of the laminated portion.

[0067] The time of the humidification treatment is preferably 6 hours or more, more preferably 12 hours or more, and even more preferably 24 hours or more. With such a treatment time, for example, the desired weight gain (water absorption) can be satisfactorily achieved. On the other hand, the time of the humidification treatment is, for example, 150 hours or less. Even if the time of the humidification treatment is excessively long, the effect will not change, so the upper limit of the time of the humidification treatment can be determined by balancing the desired amount of weight gain and production efficiency.

[0068] During the humidification process, the laminate is placed with its main surface at an angle to the placement surface. Fig. 5 is a cross-sectional view showing an example of the state in which the laminate is placed on the placement surface. In Fig. 5, hatching is omitted from the cross section of the laminate to make the drawing easier to see. In the illustrated example, the laminate 100 is placed on the placement surface S such that the main surface 100a of the laminate 100 forms an angle θ with the placement surface S. The angle θ is greater than 0° and equal to or less than 90°, preferably 70° to 90°, and more preferably 80° to 90°.

[0069] In the illustrated example, n sheets of the laminate 100 are arranged so that the main surfaces of adjacent laminates 100 overlap. Typically, prior to the humidification treatment, the laminate is cut into sheets of a predetermined size. The sheet-shaped laminate is preferably obtained by cutting a long laminate precursor. Specifically, it is preferable to obtain a sheet-shaped laminate precursor by cutting the long laminate precursor, and then laminate the first protective film and the second protective film on the sheet-shaped laminate precursor to obtain a sheet-shaped laminate. According to such an embodiment, for example, a large-scale roll conveying (roll-to-roll) facility is not required, so that the manufacturing efficiency can be improved. It is preferable to cut the laminate precursor having warpage so that the obtained sheet-shaped laminate is superimposed on the laminate precursor as shown in FIG. 5. In one embodiment, the long laminate precursor is cut along a direction at 45° to the longitudinal direction. In another embodiment, the long laminate precursor is cut along the longitudinal direction and the width direction (direction perpendicular to the longitudinal direction).

[0070] According to this embodiment, moisture can be efficiently absorbed into the laminate (polarizer), and a retardation layer-attached polarizing plate with suppressed warping can be manufactured with good yield. Specifically, by adopting a state in which the main surface of the laminate has an angle with respect to the mounting surface, as shown in FIG. 5, a humidification treatment can be performed on a plurality of laminates at once in a uniform state (for example, a state in which the force applied to the laminate is uniform), as shown in FIG. 5. As a result, moisture can be uniformly imparted to a plurality of laminates (for example, a single humidification treatment can satisfactorily achieve an increase in weight of the laminated portion of the polarizing plate and the retardation layer in a plurality of laminates), and a retardation layer-attached polarizing plate with suppressed warping can be manufactured with good yield. In addition, the obtained retardation layer-attached polarizing plate can also have an excellent appearance. EXAMPLES

[0071] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thickness and moisture permeability are values ​​measured by the following measuring methods. Furthermore, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Moisture permeability> The moisture permeability was determined by the cup method (JIS Z 0208).

[0072] [Example 1] (Preparation of polarizing plate) As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of this resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a laminate having a resin substrate / polarizer structure was obtained.

[0073] An HC-COP film (thickness 27 μm) was attached as a protective layer to the polarizer side of the obtained laminate via an ultraviolet-curable adhesive. The HC-COP film is a film in which an HC layer (thickness 2 μm) is formed on a cycloolefin resin (COP) film (thickness 25 μm), and the COP film was attached to the polarizer side. Next, the resin substrate was peeled off from the polarizer to obtain a polarizing plate having a configuration of HC-COP film (protective layer) / polarizer.

[0074] (Preparation of Retardation Layer) A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka]

[0075] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90°C for 2 minutes. The liquid crystal layer thus formed was then irradiated with 1 mJ / cm using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal with light, forming a liquid crystal alignment layer A (H layer) on the PET film. The liquid crystal alignment layer A had a thickness of 2.5 μm and an in-plane retardation Re(550) of 270 nm. Furthermore, the liquid crystal alignment layer A showed a refractive index characteristic of nx>ny=nz.

[0076] A liquid crystal alignment layer B (Q layer) was formed on a PET film in the same manner as above, except that the coating thickness was changed and the orientation treatment direction was set to a 75° direction from the viewing side with respect to the absorption axis direction of the polarizer. The thickness of the liquid crystal alignment layer B was 1.5 μm, and the in-plane retardation Re (550) was 140 nm. Furthermore, the liquid crystal alignment layer B showed a refractive index characteristic of nx>ny=nz.

[0077] (Preparation of Laminate) The obtained liquid crystal alignment solidified layer A (H layer) and liquid crystal alignment solidified layer B (Q layer) were transferred in this order onto the polarizer side of the obtained polarizing plate. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer A was 15°, and the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer B was 75°. Each transfer was performed via an ultraviolet-curing adhesive (thickness 1.0 μm). In this way, a laminate precursor was obtained. The transfer (lamination) was performed while transporting with a roll. Furthermore, the transfer (lamination) was performed in a liquid crystal display with a water vapor content of 9.3 g / m 3 The experiment was carried out under the following conditions: 23°C and 45% RH. The total thickness of the obtained laminate precursor was 36 μm, and the thickness ratio was 8.

[0078] The obtained long laminate precursor was cut in a direction at 45° to the longitudinal direction and the width direction (direction perpendicular to the longitudinal direction) to obtain a 165 mm x 80 mm sheet of laminate precursor. The longitudinal direction corresponds to the absorption axis direction of the polarizer.

[0079] Next, a surface protective film (thickness 48 μm) was attached to the protective layer side of the polarizing plate of the laminate precursor. The surface protective film was a PET film (thickness 38 μm, moisture permeability 18 g / m 2 This film has an adhesive layer (thickness 10 μm) formed on the coated film (24 h). Furthermore, a separator (thickness 38 μm, moisture permeability 18 g / m 2The laminated sheets (165 mm × 80 mm long) were laminated together with an adhesive layer (thickness: 15 μm) to obtain a laminated sheet having dimensions of 165 mm × 80 mm. Similarly, a total of 500 sheet-shaped laminates measuring 165 mm x 80 mm were prepared.

[0080] (humidification treatment) Five hundred of the obtained sheet-like laminates were stacked to form a laminate assembly, and the laminate was subjected to a humidification treatment in a state where the main surface of each laminate was placed at an angle of 90° with respect to the placement surface as shown in FIG. 5. Specifically, 500 laminates (laminate assembly) were housed in a case having a predetermined size, and the humidification treatment was performed in a state where the main surface of each laminate was placed at an angle of 90° with respect to the inner bottom surface (placement surface) of the case. Here, the humidification treatment was performed in a state where the long side of each laminate was in contact with the inner bottom surface of the case, and the empty space in the case (the space between the main surfaces of the laminates located at the front and rear ends of the laminate assembly and the inner side surface of the case) was filled with unfoamed polystyrene (PS) sheets. The humidification treatment was performed at 23°C and 60% RH (water vapor amount of 12.4 g / m 3 ) for 24 hours. In this way, a polarizing plate with a retardation layer was obtained.

[0081] [Example 2] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that a TAC film (thickness: 27 μm) was used as the protective layer instead of the HC-COP film in the production of the polarizing plate.

[0082] [Comparative Example 1] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the long laminate precursor was not cut and that the long laminate was produced and wound into a roll and subjected to the humidification treatment.

[0083] [Comparative Example 2] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that in the humidification treatment, the laminate assembly was placed so that the main surface of each laminate was at an angle of 0° with respect to the mounting surface (500 laminates were stacked and placed on the mounting surface).

[0084] [Comparative Example 3] Humidification was performed at 23°C and 45% RH (water vapor content 9.3 g / m 3 ) for 24 hours in the same manner as in Example 1, to obtain a polarizing plate with a retardation layer.

[0085] [Reference example 1] A long roll of a 60 μm thick PVA resin film was uniaxially stretched in the longitudinal direction by a roll stretching machine so that the total stretch ratio was 6.0 times, while simultaneously undergoing swelling, dyeing, crosslinking and washing treatments, and finally drying treatment to produce a polarizer with a thickness of 22 μm. A TAC film (thickness 71 μm) with an HC layer was laminated to one side of the obtained polarizer. Furthermore, a polycarbonate resin retardation film (thickness 58 μm) showing reverse dispersion wavelength dependency and having Re (550) of 140 nm was laminated to the other side of the polarizer. Here, the retardation film was laminated so that the angle between the slow axis of the retardation film and the absorption axis of the polarizer was 45°. In this way, a polarizing plate with a retardation layer was obtained. The total thickness of the polarizing plate with a retardation layer was 151 μm, and the thickness ratio was 1.6. This polarizing plate with a retardation layer was cut into a size of 165 mm x 80 mm and placed on a flat surface, and no warping was observed.

[0086] [Reference example 2] A polarizer having a thickness of 22 μm was produced in the same manner as in Reference Example 1. A TAC film with an HC layer (thickness 91 μm) was attached to one surface of the obtained polarizer, and a TAC film (thickness 80 μm) was attached to the other surface to obtain a polarizing plate. A polarizing plate with a retardation layer having a structure of a TAC film with an HC layer / polarizer / TAC film / adhesive layer / retardation layer (H layer) / adhesive layer / retardation layer (Q layer) was obtained in the same manner as in Example 1, except that this polarizing plate was used. The total thickness of the polarizing plate with a retardation layer was 197 μm, and the thickness ratio was 48. This polarizing plate with a retardation layer was cut into a size of 165 mm×80 mm and placed on a flat surface, and no warping was observed.

[0087] The following evaluations were carried out for the Examples and Comparative Examples. The evaluation results are summarized in Tables 1 and 2. <Evaluation> 1. Weight change per unit area The weight of the laminated portion from the polarizing plate to the pressure-sensitive adhesive layer (laminate portion 80 shown in FIG. 4) was measured using an electronic balance before and after humidification, and the weight was calculated from the obtained measured values. 2. Amount of warping The laminate precursor and the retardation layer-attached polarizing plate in the form of a sheet were placed on a flat surface with the retardation layer side facing the flat surface, and the height of the highest part from the flat surface was measured to obtain the amount of warping. In addition, when the warp is convex toward the stationary surface, it is represented as "positive (+)", and when it is convex toward the opposite side to the stationary surface, it is represented as "negative (-)". In the table, "(MD)" corresponds to the transport direction of the roll transport and corresponds to the absorption axis direction of the polarizer. 3.Appearance The appearance of the obtained polarizing plate with a retardation layer was visually observed and evaluated according to the following criteria. (Evaluation Criteria) Good: No dents observed Defective: Dents are found

[0088] [Table 1]

[0089] [Table 2]

[0090] As is clear from Table 1, in Examples 1 and 2, the weight change due to the humidification treatment was confirmed to be within the range of 0.1% to 0.4%, and the warpage of the obtained retardation layer-attached polarizing plate was within the range of -20mm to +20mm (- indicates warpage in the MD direction, and + indicates warpage in the TD direction perpendicular to the MD direction). Thus, in Examples 1 and 2, moisture could be uniformly added to multiple laminates, and the degree of correction of the warpage generated in the laminate precursor was also highly uniform. In contrast, in Comparative Example 2 in which the laminates were placed on the mounting surface, variation in weight change due to humidification treatment was confirmed. Specifically, the laminates located at the top of the laminate assembly were subjected to a smaller force than the laminates located at the bottom, and the laminates located at the top absorbed more moisture than the laminates located at the bottom, and the laminates located at the top were confirmed to have a warp in the opposite direction to the warp that occurred in the laminate precursor. On the other hand, the warp that occurred in the laminate precursor was improved in the laminates located at the bottom. Thus, variation was confirmed in the degree of correction of the warp that occurred in the laminate precursor. In addition, dents were also confirmed in the obtained retardation layer-attached polarizing plate.

[0091] In Comparative Example 1, in which the film was subjected to a humidification treatment in a rolled state, the weight per unit area of ​​the inner part wound in the roll did not change, and warping was not improved. As is clear from the reference examples, such warping is a problem specific to polarizing plates with a retardation layer, which have a small total thickness and a large ratio of the thickness of the polarizing plate to the total thickness. [Industrial Applicability]

[0092] The retardation layer-attached polarizing plate according to one embodiment of the present invention is used as a retardation layer-attached polarizing plate for an image display device, and can be particularly suitably used for a curved, bent, foldable, or rollable image display device. Representative examples of the image display device include a liquid crystal display device, an organic EL display device, and an inorganic EL display device. [Explanation of symbols]

[0093] 10 Polarizing plate 11 Polarizer 12 Protective layer 20 Retardation layer 21 First retardation layer (H layer) 22 Second retardation layer (Q layer) 90 Laminate precursor 100 Laminate

Claims

1. preparing a laminate having, in this order, a first protective film, a polarizing plate including a polarizer and a protective layer disposed on at least one side of the polarizer, a retardation layer, and a second protective film, the sum of the thickness of the polarizing plate and the thickness of the retardation layer being 50 μm or less, and the ratio of the thickness of the polarizing plate to the thickness of the retardation layer being 5 or more; and In a state where the laminate is placed on a placement surface, the laminate is subjected to a steam pressure measurement in which the amount of water vapor is 10.5 g / m 3 The above-mentioned environment is subjected to humidification treatment. preparing the laminate includes laminating the polarizing plate and the retardation layer using an active energy ray-curable adhesive; The laminate is placed with a main surface of the laminate at an angle to the placement surface, The humidification treatment is performed in a state where a plurality of the laminates are arranged so as to overlap each other. A method for producing a polarizing plate with a retardation layer.

2. The method according to claim 1 , further comprising laminating the polarizing plate and the retardation layer to obtain a laminate precursor.

3. The method according to claim 2 , further comprising cutting the laminate precursor into sheets.

4. The first protective film has a moisture permeability of 30 g / m at 40° C. and 92% RH. 2 The method according to any one of claims 1 to 3, wherein the period is 24 hours or less.

5. The second protective film has a moisture permeability of 30 g / m at 40° C. and 92% RH. 2 The method according to any one of claims 1 to 4, wherein the period is 24 hours or less.

6. The method according to claim 1 , further comprising laminating the polarizing plate and the retardation layer while transporting them with a roll.

7. The method according to claim 1 , wherein the active energy ray-curable adhesive has a thickness of 0.4 μm or more after curing.

8. the laminate has a pressure-sensitive adhesive layer disposed on a side of the retardation layer on which the polarizing plate is not disposed, The method according to claim 1 , wherein the humidification treatment increases a weight per unit area of ​​the laminate of the polarizing plate, the retardation layer and the pressure-sensitive adhesive layer by 0.1% or more.

9. The method according to claim 1 , wherein the humidification treatment is carried out for 6 hours or more.

10. The amount of water vapor during the humidification treatment was 10.5 g / m 3 ~30g / m 3 The method according to any one of claims 1 to 9,

11. The polarizing plate and the retardation layer were heated to a temperature of 10.2 g / m 3 The method of any one of claims 1 to 10, comprising laminating under the following conditions:

12. The amount of water vapor during the humidification treatment is 0.5 g / m less than the amount of water vapor during lamination of the polarizing plate and the retardation layer. 3 The method according to claim 1 , wherein the concentration of the at least one stoichiometric amount ...

13. The moisture permeability of the retardation layer or the protective layer at 40° C. and 92% RH is 300 g / m 2 The method according to any one of claims 1 to 12, wherein the period is 24 hours or more.

14. The method according to claim 1 , wherein the polarizing plate has a protective layer disposed only on a side of the polarizer on which the retardation layer is not disposed.

15. The method according to claim 1 , wherein the center of gravity of the polarizer in the thickness direction is located closer to the retardation layer than the center of gravity of a laminated portion of the polarizing plate and the retardation layer in the thickness direction.

16. The method according to claim 1 , wherein the retardation layer is a layer in which a liquid crystal compound is aligned and fixed.

Citation Information

Patent Citations

  • Method and installation for manufacturing retardation film

    JP2010134440A

  • Laminated glass production method

    JP2019069865A

  • Retardation film and optical device using the same

    JP3325560B2

  • Film manufacturing method and film

    WO2017111048A1

  • Organic electroluminescence display device

    WO2019022156A1